THE EDUCATOR STRESS RESILIENCE AND THE QUALITY OF THE EDUCATIONAL PROCESS (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
This article analyzes the issue of educators’ stress resilience based on modern psychological and pedagogical approaches. The causes of stress arising in educators’ professional activities and their impact on personality psychology and professional performance are examined. In addition, the article scientifically substantiates how educators’ stress resilience affects the quality of the educational process, children’s emotional states, and social adaptation. Effective psychological mechanisms and practical recommendations for developing stress resilience are proposed.